Impact of Corona Virus on African Economic Growth - Abdel Razek Youssef, Abeer Mohamed (Asian Journal of Science and Applied Technology, 2021)
The COVID-19 crisis is affecting the entire world economy and that of Africa. Some key sectors of the African economy are already experiencing a slowdown because of the pandemic. Tourism, air transport, and the oil sector are visibly impacted. The exogenous effects come from direct trade links between affected partner continents such as Asia, Europe and the United States; tourism; the decline in remittances from African Diaspora; Foreign Direct Investment and Official Development Assistance; illicit financing flows and domestic financial market tightening, etc. The endogenous effects occur because of the rapid spread of the virus in many African countries. On one hand, they are linked to morbidity and mortality. On the other hand, they lead to a disruption of economic activities. This may cause, a decrease in domestic demand in tax revenue due to the loss of oil and commodity prices coupled with an increase in public expenditure to safeguard human health and support economic activities. This study aims to evaluate the potential impact of the pandemic on various dimensions of African economies, the impact on the African economy is presented, with a discussion of some of the key measures being taken by African Union to mitigate the negative effects.